Lactobacillus casei-fermented blueberry pomace augments sIgA production in high-fat diet mice by improving intestinal microbiota. Issue 7 (9th July 2020) - Cheng, Yuxin; Tang, Shuxin; Huang, Yuting; Liang, Fuqiang; Fang, Yajing; Pan, Siyi; Wu, Ting; Xu, Xiaoyun
Abstract : Intestinal secretory immunoglobulin A (sIgA)-improving function of Lactobacillus casei -fermented blueberry pomace (FBP) was investigated in this study. Abstract : Intestinal secretory immunoglobulin A (sIgA)-improving function of Lactobacillus casei -fermented blueberry pomace (FBP) was investigated in this study. Male C57BL/6 mice were fed with control diet (CD) or high-fat diet (HFD) with or without FBP supplementation. Expressions of sIgA-associated genes/proteins were evaluated by quantitative polymerase chain reaction (qPCR), western blot and enzyme-linked immunosorbent assay (ELISA). Commensal microbiota in Peyer's patches (PPs) and caecal contents were analyzed by 16S rRNA Illumina sequencing and qPCR, respectively. FBP improved sIgA production in HFD mice at mRNA and protein levels. Akkermansia and Lactobacillus in PPs of HFD mice were statistically increased by FBP. Beneficial microbiota and short-chain fatty acids (SCFAs) in caecal contents were positively correlated with caecal immunoglobulins in HFD mice. FBP showed an ability to modulate intestinal microbiota, which improved sIgA production in HFD mice, warranting the potential use of berry by-products as functional ingredients in improving the intestinal immune barrier of HFD individuals.